Trends in cultured meat: a bibliometric and sociometric analysis of publication - Fernandes, Alice Munz; Fantinel, Antonio Luiz; Souza, Ângela Rozane Leal de; Révillion, Jean Philippe Palma (Faculdade de Filosofia e Ciências, 2019)
The cellular agriculture is been considered as a mechanism to minimize future negative impacts from the estimated world population growth for the coming decades. Among the alternatives of this technology, the development of meat grown in the laboratory stands out. Numerous researchers have been making efforts to develop this scientific field today. However, few studies have tried to map the intellectual panorama and emerging themes in the scientific literature of this scientific field. Thus, this research aims to analyze from the perspective of the bibliometric and sociometric analysis the scientific publications on meat cultivated within the perspective of cellular agriculture, indexed in the Web of Science database. We analyzed 91 publications on cultured meat, combining mapping data, patterns of co-citation and collaboration from scientific journals and authorship. We also analyze emerging issues in the research on meat cultivated. We noted that, given the participation of authors and co-authors from different areas of knowledge, there is not a pattern in the composition of collaboration networks. Also stands out the multidisciplinary nature of the studies on cultured meat, transposing different disciplines and analytical approaches. Those aspects concerning the environmental, cultural impact, technical viability of its productive process and impacts on traditional livestock production appear as latent constructs in this new food biotechnology.